Mechanisms of microvoid formation within KCl single crystals in the pulse energy release area of laser focused radiation - Boyko, Yu.I.; Volosyuk, M.A.; Kononenko, V.G. (Functional Materials, 2012)
Mechanism of micropore formation in the area of pulse energy release of the laser focused radiation in KCI single crystals was studied experimentally at low (77 K) and room (300 K) temperatures. The pulse duration was varied from 510⁻⁸ s to 10⁻³ s and pulse energy — from 1 to 20 J. The observed pore sizes were (0.75 ÷ 120)*10⁻⁶ m. The dislocation structure around the pores and photo-elastic stress pattern were studied. For the experimental results obtained the following values were estimated: the initial pressure in the relaxation area (2*10⁹N/m²), the heated-up "nucleus" temperature (1100 K), and the laser pulse absorbed energy corresponding to a given pore size. As it is seen from the experiments, the dislocation mechanism contribution into the substance transport for pore sizes less than 10⁻⁵ m is 2 ÷ 4 %, while the rest of substance is taken away by crowdion (interstitial atom) mechanism. The diffusion contribution into the mass transport is found to be negligible.